The Importance of Bank Seniority for Relationship Lending - Longhofer, Stanley D.; Santos, João A.C. (Journal of Financial Intermediation, 2000)
The idea that banks exist to reduce the costs of monitoring is central to modern theories of financial intermediation. The fact that banks are generally granted senior positions on their small-business loans, however, is hard to reconcile with the typical view that junior lenders have the best incentives to engage in this costly monitoring. Our paper addresses this puzzling contradiction by showing that bank seniority plays an important role in encouraging the formation of valuable bank–firm relationships. The intuition behind our model lies in the fact that once the firm's prospects have deteriorated, junior creditors have incentives much like those of the firm's shareholders. Thus, it is the most senior claimant that benefits from helping the firm improve its quality. If banks are made junior to other creditors, they benefit little from additional investment in the firm during times of poor performance and hence will have little incentive to build relationships that enable them to determine the value of such an investment. As a result, making the bank senior improves its incentives to build a relationship with the firm, thereby fulfilling an important function of intermediated debt. Journal of Economic Literature Classification Numbers: G21, G32.